PELAKSANAAN FULL DAY SCHOOL SEKOLAH DASAR ISLAM TERPADU AL HUDA KECAMATAN SANGKAPURA KABUPATEN GRESIK (Studi Problematika Perkembangan Sosial Peserta Didik) - Purnama Susiati; Ali Asyhar (CENDEKIA: Jurnal Studi Keislaman, 2015)
This research studies about problems of full-day school implementation in SDIT Al Huda Sangkapura Gresik. The focus of study is how the impact of full day school to the social development of students is. It also discusses about obstacles faced by many teachers and solutions that teachers were doing in helping social development of students. This study assessed qualitatively by a phenomenological approach. The whole is descriptive studies in which researchers describe the research activities carried out at the object clearly and systematically. The Results of this study showed that the implementation of full day school in SDIT Al-Huda in its learning system, in general, is similar to that implemented in the pesantrens. The difference lies in the proportion of the learning system that is quantity of learning between general and religious matter each 50%. Another difference is the students do not live in school dormitory. The problems faced by the students in SDIT Al-Huda when compared with students who attend school regularly is the lack of social interaction with the community. The students have a feeling of inferiority, and lack of social sensitivity. In another side, the problems faced by teachers in helping social development of the students is the lack of parental support in motivating them to participate in school activities, lack of funds owned SDIT Al Huda, and lack of professionalism of teachers in a fun method. The solutions which teachers were doing to solve the social development problems, among other learners accustomed salutation, formed a partnership with parents, study visits to other institutions, familiarize prayers in congregation, held a talent development program and interests, and to visit a sick friend’s home. Hopefully, through this research arose an idea to improve the condition of existing education. The development of students like to be balanced between the academic and social.